How nurses’ moral competence can be supported: Findings from international focus groups with professionals - Wiisak, Johanna; Suhonen, Riitta; Galazzi, Alessandro; Gastmans, Chris; Keogh, Brian; Papastavrou, Evridiki; Stefanopoulos, Nikos; Palese, Alvisa; Stolt, Minna; PROMOCON Consortium (Wiley, 2025)
Aim
To describe how nurses’ moral competence can be supported from the perspective of nurses, nurse managers, researchers, educators, and nursing students.
Background
Moral competence is the capacity or ability of nurses to recognise one's own emotions of what is right or wrong, to reflect on these emotions, to make decisions, and to act in ways that bring the highest level of benefit to patients. Moral competence is part of professional competence. However, little is known about how nurses’ moral competence can be supported.
Methods
A qualitative descriptive study design was applied. Stratified purposive sampling was employed and focus group discussions were conducted in Belgium, Cyprus, Finland, Greece, Ireland, and Italy in 2023. A total of 38 informants (5–8 per focus group) who were registered nurses or nursing students participated. The data were analysed using both deductive and inductive content analysis. The COnsolidated criteria for REporting Qualitative research were adhered to.
Results
Seven themes were developed following analysis, which suggested that support for nurses’ moral competence can be located at individual-relational, organisational, and societal levels. Several approaches and/or tools were also identified to support moral competence.
Conclusion
Nurses’ moral competence could benefit from continuous support from colleagues, those in leadership positions, organisations and society. Practical tools and approaches can also successfully support nurses’ moral competence.
Implications for nursing and health policy
Support for nurses’ moral competence forms a continuum from the beginning of nursing studies throughout nursing careers. Thus, educational interventions and training programmes are needed both at basic and continuous ethics education. There is also a need for investments in and development of strategies and regulations on ethics management in health systems, national- and international-level ethics indicators for health policy-making, and implementation of existing practices, interventions, and procedures in nursing practice.